Pragmatics and Logic: Some examples of an effective interaction - Алексюк, І.А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2012)
This article investigates the possibility of applying the theory of implicature communication to the interpretation of a number of logical problems: truly functional interpretation of logical and grammatical connectors, rasselivska logical form defined deskryptsiy, paradox Moore.